Different sources of selenium added to whole corn grain diet in the finishing phase of Angus steers (Research, Society and Development, 2020)
Selenium is an essential cofactor for antioxidant enzymes. Among the sources available on the market, sodium selenite (inorganic source) is the most used and studied; nevertheless, organic sources have been described as being more efficient. Against this background, the objective of the present study was to determine whether various selenium sources, both inorganic (sodium selenite) and organic (selenomethionine), in the whole grain feed for finishing Angus steers would affect performance as well as carcass and meat quality. For this purpose, 22 animals were selected and were divided as follows: sodium selenite group (SS = 11) and selenomethionine group (SM = 11). The feedlot period was 82 days, with 15 days of adaptation and a total of four weighings. We measured carcass weight, slaughter temperature, and pH, after 24 h carcass yield, cooling loss, pH, color, and subcutaneous fat thickness. Longissimus thoracis muscle samples were taken between 12th and 13th ribs of the left half carcass to measure muscle width and depth, rib-eye area, meat color and pH at 24 hours and 48 hours, in addition to other laboratory analyses, including tenderness, cooking losses, thiobarbituric acid reactive substances, and selenium concentration analysis. There were no differences between groups with respect to performance or carcass and meat quality, as well selenium concentration and freezing time. These findings suggest that both selenium sources can be used in whole grain feed for finishing Angus steers and that they have the same effects on performance and carcass and meat quality.